Phase formation, microstructure and magnetic properties of (1-x)BiFeO 3-x(0.9Pb(Mg1/3Nb2/3)O3-0. 1PbTiO3) system - Wongmaneerung R. (2014)
Multiferroic composites containing bismuth ferrite (BF) and lead magnesium niobate-lead titanate (0.9PMN-0.1PT) phases were fabricated by solid-state reaction, with 10-50 wt% of 0.9PMN-0.1PT. The phase formation behavior and microstructural features were investigated by X-ray diffraction (XRD) and scanning electron microscopy (SEM), respectively. Information on the oxidation state of Fe ions was determined by the synchrotron X-rays absorption near edge structure (XANES) technique. A vibrating sample magnetometer (VSM) was used to characterize the magnetic properties. The results indicated that all composites showed a perovskite structure and the PMN-PT phase was compatible with the BF phase. The microstructure displayed mixed BF, PMN and PT phases. In addition, the presence of secondary phases (Bi2Fe4O9 and Fe2O3) was observed by both XRD and XANES techniques. The presence of BF, Bi2Fe4O9 and Fe 2O3 phases was also confirmed by the oxidation state and the local structure surrounding the Fe absorbing atom, as observed in the Fe K-edge XANES spectrum. Moreover, the composites exhibited typical magnetic hysteresis (M-H) loops at room temperature. The maximum saturation magnetization (MS) was observed for x=30 and 40 wt%. © 2013 Elsevier Ltd and Techna Group S.r.l.